ANALYSIS OF HOSPITAL INFORMATION MANAGEMENT SYSTEM USING HUMAN ORGANIZATION FIT MODEL - Husnaina Febrita; Martunis Martunis; Dedy Syahrizal; Munifah Abdat; Bakhtiar Bakhtiar (Universitas Airlangga, 2021)
Background: Hospital is a health care institution that provides public services for patients. It needs computerized information technology, for example, a hospital information management system.Aims: This study was aimed at analyzing the implementation of hospital management information system using the human organization fit model at the Outpatient Department of Sabang General Hospital.Methods: This study was conducted from March-June 2020 using a cross sectional design. The study’s population was the hospital managers, administration staff and health workers at the hospital. The study’s sample size was 106 respondents selected using a purposive sampling. This study used a quantitative design in which the data analysis was done using a spearman correlation test with P-value of =<0.05. The independent variables were the quality of system, quality of information, and quality of care. While the dependent variables included system user, user satisfaction and organization. The data were collected through questionnaire distributed to the respondents.Results: The quality of system did not have a relationship with the system user (P=0.585), user satisfaction (P=0.541), and organization (P=0.256). The quality of information had a relationship with the system user(P=0.004) and user satisfaction (P=0.000), but it did not have a relationship with organization (P=0.132). The quality of care had a relationship with the system user(P=0.000), user satisfaction (P=0.000) and organization (P=0.000).Conclusion: The Sabang General Hospital, Aceh, needs to improve the hospital management information system with the HOT-fit model, especially the quality of system. They can conduct training for users and provide applicable and attractive manuals.Keywords: hospital, information management system, quality of care, quality of information, quality of system.